Persepsi Petani terhadap Dampak Sosial Dalam Adopsi Teknologi Combine Harvester terhadap Petani Padi di Kecamatan Rambutan Kabupaten Banyuasin - Henny Malini; Nukmal Hakim; Erni Purbiyanti; Mekanidianti Mekanidianti (Seminar Nasional Lahan Suboptimal, 2018)
Malini et al, 2019. Farmers' Perception of Social Impacts in Adoption of Combine Harvester Technology on Rice Farmers in Rambutan District Banyuasin Regency. pp. 260-269. The use of Combine harvester is considered as a form of efficiency, it harvesting can be faster and cheaper, using Combine harvester is the hope that the government will be able to increase the productivity gained by farmers, but on the contrary without paying attention to the social environment in the village will create problems for the workers in the village because the existing energy absorption is uneven, and this will have a social impact.  The reasearch aimed to study farmers' perception of social impacts in adoption  of combine harvester technology on rice farmers in Rambutan District Banyuasin Regency.  This research was carried out for one year in Rambutan Subdistrict, Banyuasin Regency in South Sumatra. Primary and secondary data collection is carried out in May to July 2018. Implementation of activities includes collection of secondary data and primary data. Two villages were chosen in this sub-district, and from each village a sample of rice farmers was considered to be able to represent the population in Simple Random Sampling. Based on the results of the study showed that the use of Combine Harvester technology did not significantly affect the social life of farmers, meaning that the impact was in good category. indicators of social economic impact seen from the mutual assistance variables, the level of security of farmers, relationship / friendship among farmers, community groups.